2012
DOI: 10.1007/s00415-011-6383-4
|View full text |Cite
|
Sign up to set email alerts
|

Delirium in acute stroke: screening tools, incidence rates and predictors: a systematic review

Abstract: Abstract:Background and purpose: Delirium is a common complication in acute stroke yet there is uncertainty regarding how best to screen for and diagnose delirium after stroke. We sought to establish how delirium after stroke is identified, its incidence rates and factors predicting its development. Methods: We conducted a systematic review of studies investigating delirium in acute stroke. We searched The Cochrane Collaboration, MEDLINE, EMBASE, CINHAL, PsychINFO, Web of Science, British Nursing Index, PEDro … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
47
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 94 publications
(55 citation statements)
references
References 41 publications
5
47
3
Order By: Relevance
“…Prevalence of delirium is 10.7%, giving a lower prevalence than 26% in a recent meta-analysis (Carin-Levy et al, 2012). There are different hypothesis' to explain this result.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Prevalence of delirium is 10.7%, giving a lower prevalence than 26% in a recent meta-analysis (Carin-Levy et al, 2012). There are different hypothesis' to explain this result.…”
Section: Discussionmentioning
confidence: 91%
“…The etiology of delirium is complex, and current theories explain its development by interaction of hypoxia, inflammatory processes, disturbance of neurotransmitter, and the presence of internal or external risk factors (Riedel, Browne, & Silbert, 2014). The prevalence of delirium in patients after stroke is estimated to average 26% (Carin-Levy, Mead, Nicol, Rush, & van Wijck, 2012). A delirium increases the risks for mortality, complications, longer length of hospital stay, and institutionalization (Shi, Presutti, Selchen, & Saposnik, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Our systematic review [4] identified a number of tools commonly mentioned in the literature; however, the most frequently cited are the Delirium Rating Scale (DRS) [25] and the CAM [24], both of which are based on the American Psychiatric Association diagnostic and statistical manual (DSM) criteria and designed to identify delirium across a variety of medical settings. The DRS was designed to be used by medical staff with specific training [25].…”
Section: Description Of Screening/diagnostic Toolsmentioning
confidence: 99%
“…In acute stroke, the incidence of delirium reported by individual studies ranges from 10% [2] to 48% [3], and meta analyses recently performed placed the incidence around 26%-28% [4,5]. Delirium is associated with increased mortality, morbidity, and length of hospital stay [5][6][7][8], and it has been strongly associated with development of cognitive impairment in the long term in the general medical setting [9,10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation